On the estimation of ice volume of alpine glaciers - Yu. Macheret Ya.; S. Kutuzov S.; V. Matskovsky V.; I. Lavrentiev I.; Ю. Мачерет Я.; С. Кутузов С.; В. Мацковский В.; И. Лаврентьев И. (Pirineos, 2015)
Volume (V) − area (S) scaling approach (V = kSp, where V and S are obtained from direct measurements) is widely used for ice storage assessments in glacier-mountain systems. Accuracy of this approach was tested using surface area and volume dataset for 121 glaciers of different morphological type and sizes in Altay Mountains. It is shown that to increase total volume estimation accuracy, the coefficients k and p should be calculated for dominant morphological glacier types in the given region. Volume assessments for individual glaciers can be done using limited ice thickness data along the longitudinal profile. For two glaciers in Caucasus volume was calculated using parabolic and Topo to Raster approximation for cross section profiles of their surface and bedrock with acceptable accuracy (from 1 to 33%). It is also shown that ice-thickness data for 10–15 glaciers of dominant morphological type is enough for adequate estimation of the total ice storage in given mountain system with error less than 20%. Имеющиеся данные по измерению толщины и объёма горных ледников, а также существующие расчётные методы не позволяют достаточно точно установить запасы льда в горно-ледниковых системах. Обсуждаются существующие методы определения объёма горных ледников и запасов льда в горно-ледниковых системах, а также способы их более точной оценки на основе ограниченных данных о толщине и объёме отдельных ледников. Оценивается ошибка определения объёма отдельных ледников при ограниченном числе измерений.